2021
DOI: 10.1111/jch.14243
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the novel Peguero Lo‐Presti criterion for electrocardiographic detection of left ventricular hypertrophy in a black African population

Abstract: Left ventricular hypertrophy (LVH), a maladaptive response to chronic pressure overload, is a marker of subclinical cardiac disease and a predictor of arrhythmias, heart failure, and death. 1,2 Because LVH is potentially reversible, its early detection and appropriate management of its underlying cause can prevent related adverse cardiovascular outcomes. 3 In routine clinical practice, LVH is usually

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A novel ECG criterion for LVH, proposed by Peguero et al [11], was recently shown to be more sensitive than traditional ECG-LVH criteria in patients with arterial hypertension. To date, the ability of the novel criterion to discriminate patients with and without anatomic LVH have been estimated in various clinical settings, including cardiac patients and the general population, demonstrating generally rather modest (and, at best, moderate) superiority over the classical ECG-LVH criteria in some [12][13][14][15][16], but not all [17][18][19][20][21][22][23]. However, to the best of our knowledge, only one study was focused on patients with aortic stenosis [24], the most prevalent valvular heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…A novel ECG criterion for LVH, proposed by Peguero et al [11], was recently shown to be more sensitive than traditional ECG-LVH criteria in patients with arterial hypertension. To date, the ability of the novel criterion to discriminate patients with and without anatomic LVH have been estimated in various clinical settings, including cardiac patients and the general population, demonstrating generally rather modest (and, at best, moderate) superiority over the classical ECG-LVH criteria in some [12][13][14][15][16], but not all [17][18][19][20][21][22][23]. However, to the best of our knowledge, only one study was focused on patients with aortic stenosis [24], the most prevalent valvular heart disease.…”
Section: Introductionmentioning
confidence: 99%